Integration by Sport and Physical Activities in Europe: An Introduction - Giovanna Russo; William Gasparini (Culture e Studi del Sociale)
Sport is traditionally presented and used as a vector of integration and citizenship for foreign populations in all immigration countries. Leisure sports activities allow intercultural dialogue and offer opportunities for socialization. For this reason, in several European countries, sports associations and NGOs have initiated many sports programs open to migrants and refugees, the effects of which are often unknown to social science. Furthermore, the issue of welcoming migrants has taken on a new dimension in recent years: Europe is the region that quantitatively welcomes the largest number of international migrants. In this context, the use of sport to integrate newly arrived migrants raises many questions for social sciences. Can we thus identify practices and initiatives for integration through sport that can be generalized to all countries? How do the different European countries deal with the migratory phenomenon and with what reception arrangements and integration models? Comparing several sporting practices, programs and systems in different countries the paper investigates how inclusion and integration are translated into action strategies, and suggests a rethinking of some sociological categories. Doing so, the concepts of Integration, immigrant, migrant and sport are tested by Social Sciences in order to better understand the society we are living.